Field reports form for submitting seasonal observations of Iowa birds, Eugene & Eloise Armstrong, fall 1994 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1994)
An annotated list of birds sighted by Eugene and Eloise Armstrong. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1994. Plustek - flatbed